what solution is y= 3x + 6, y= -13x - 4

1 answer

To find the solution to the system of equations given by \( y = 3x + 6 \) and \( y = -13x - 4 \), we can set the two equations equal to each other since they both equal \( y \):

\[ 3x + 6 = -13x - 4 \]

Now, we will solve for \( x \):

  1. Add \( 13x \) to both sides: \[ 3x + 13x + 6 = -4 \] \[ 16x + 6 = -4 \]

  2. Subtract 6 from both sides: \[ 16x = -4 - 6 \] \[ 16x = -10 \]

  3. Divide by 16: \[ x = -\frac{10}{16} = -\frac{5}{8} \]

Now that we have \( x \), we can substitute it back into either equation to find \( y \). We will use the first equation \( y = 3x + 6 \):

\[ y = 3\left(-\frac{5}{8}\right) + 6 \] \[ y = -\frac{15}{8} + 6 \] \[ y = -\frac{15}{8} + \frac{48}{8} \] \[ y = \frac{48 - 15}{8} = \frac{33}{8} \]

So the solution to the system of equations is:

\[ \left( -\frac{5}{8}, \frac{33}{8} \right) \]